SYAR’I AND ASTRONOMY INTEGRATION TO DETERMINE THE BEGINNING OF HIJRI CALENDAR: A Study of Elongation to Prove the Hilâl Testimony - Muhammad Nurkhanif; Azmi Muttaqin; Ali Imron; Mohd Razlan Ahmad (ULUL ALBAB Jurnal Studi Islam, 2022)
This article was motivated by the fact that most observers in Indonesia are inconsistent in determining the theoretical and practical beginning of the Hijri month. They only consider the aspect of the height of hilâl, but ignore the angle of elongation during the process of observing hilâl. This inconsistency occurs in the theory and practice reflected in the Decision of the Ministry of Religious Affairs of the Republic of Indonesia. Based on this case, the authors want to analyze the decision, especially the data on the testimony stating that the new moon (hilâl) can be successfully seen, as received from 1962 - 2021 M. The type of research used is qualitative and descriptive using the data analysis technique adapted from the Millis and Huberman theory to obtain the data classification of that decision by using the scientific cum doctrine approach. The results of this study are first; the number of ithbât maṣlaḥî reached 45% and ithbât takâmulî reached 55% of all decrees of the Minister of Religious Affairs of the Republic of Indonesia. Second; to minimize the number of ithbât maṣlaḥî, a theory of the selection of the hilâl testimony is needed, which is known as the M2P theory.